Satisfaction-Mediated Effects of Halal Label, Product Quality, and Islamic Service on Customer Loyalty: Maqasid-Shariah Perspective - Fauzah, Nur Muammalatul; Makhtum, Ahmad (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2025)
The rapid expansion of Indonesia’s halal food industry highlights the need to understand how halal compliance, product performance, and Islamic ethical values shape consumer behavior, particularly among Generation Z. This study examines the direct and indirect effects of Halal Labeling, Product Quality, and Islamic Service on Customer Satisfaction and Customer Loyalty at Richeese Factory Indonesia, employing a mixed methods sequential explanatory design. The quantitative phase involved 100 Generation Z respondents in East Java selected through purposive sampling, with data analyzed using validity and reliability testing, classical assumption tests, multiple linear regression, and the Sobel test. The results indicate that Product Quality and Islamic Service significantly influence Customer Satisfaction, whereas Halal Labeling does not. Customer Satisfaction significantly enhances Customer Loyalty and mediates the effects of Product Quality and Islamic Service but does not mediate the influence of Halal Labeling. The qualitative interpretation, guided by maqāṣid al-sharī‘ah, reveals that while halal certification fulfills ḥifẓ al-dīn and is legally mandated by the Halal Product Assurance Law (UU No. 33/2014), loyalty is primarily shaped through ṭayyib product quality (ḥifẓ al-nafs) and ethical service practices (ḥifẓ al-māl). The study underscores the need for integrative halal management that aligns regulatory compliance with experiential value to foster sustainable consumer loyalty.Keywords: Customer Loyalty; Customer Satisfaction; Halal Label; Islamic Services; Product Quality